2017
DOI: 10.1186/s12934-017-0691-z
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects on host energy metabolism of short-chain fatty acids and vitamins produced by commensal and probiotic bacteria

Abstract: The aim of this review is to summarize the effect in host energy metabolism of the production of B group vitamins and short chain fatty acids (SCFA) by commensal, food-grade and probiotic bacteria, which are also actors of the mammalian nutrition. The mechanisms of how these microbial end products, produced by these bacterial strains, act on energy metabolism will be discussed. We will show that these vitamins and SCFA producing bacteria could be used as tools to recover energy intakes by either optimizing ATP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
418
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 658 publications
(495 citation statements)
references
References 85 publications
16
418
1
4
Order By: Relevance
“…The role of genus Prevotella in NAFLD is still controversial in human study. Several previous studies indicated that the abundance of Prevotella was reduced in the patients with NAFLD, but the reversed findings were observed by other group . The differences in environmental conditions and dietary intake might be also the crucial factors affecting the abundance of Prevotella …”
Section: Discussionmentioning
confidence: 85%
“…The role of genus Prevotella in NAFLD is still controversial in human study. Several previous studies indicated that the abundance of Prevotella was reduced in the patients with NAFLD, but the reversed findings were observed by other group . The differences in environmental conditions and dietary intake might be also the crucial factors affecting the abundance of Prevotella …”
Section: Discussionmentioning
confidence: 85%
“…A recent study indicated that the incubation of primary murine L cells with a concentration of propionate at 1.0 mmol L –1 achieved the same level of PYY secretion and about 73% of the level of GLP‐1 secretion compared to the effects of incubating cells at a propionate concentration of 50.0 mmol L –1 , which may indicate the dosage‐independence of propionate impact in cell culture. Another recent study found that 62% of infused propionate was used as gluconeogenic substrate, suggesting that, before arriving at the liver, the available propionate can be efficiently converted to monosacharide in the intestine . More importantly, propionate is highly involved in the gluconeogenesis pathways in the intestine and this process is triggered by the existence of butyric acid, because butyrate rather than propionate can directly activate genes expression associated with intestinal gluconeogenesis in enterocytes, demonstrating the interacting‐regulatory mechanism between SCFAs involved in cell metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that some commensal bacterial species and probiotic bacteria can produce many kinds of vitamins, such as vitamins in the B and K groups, folate, and nicotinic acid, which are directly involved in essential energy metabolism in the gut [30,31]. VSL#3 is manufactured with a carefully designed formulation of billions of eight strains of live freeze-dried lactic acid bacteria.…”
Section: Discussionmentioning
confidence: 99%